Implementasi Undang-Undang Nomor 15 Tahun 2016 dalam Melindungi Hak-Hak Anak Buah Kapal di PT Samudera Indonesia - Fakhrurrozi; Ridwan (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
Crew members are all people who work on the ship, who are in charge of operating and maintaining the ship and its cargo, other than the captain or ship leader. In carrying out their duties they often experience difficulties ranging from fraudulent job vacancies, violence, wages that are still below the minimum wage, to crimes of robbery and persecution. This study aims to discuss the implementation of Law No. 15. Year 2016 in protecting the rights of Ship Crew, in a case study research at PT Samudera Indonesia, Semarang branch. This research is based on empirical juridical research based on normative law science or statutory regulations. The primary data source that the writer presents is obtained from questionnaire data, the results of interviews and observations (field research) and secondary data obtained from the results of library research, by studying the rules and books related to this research. The research specification in this writing is descriptive analytical. The theory used by the author in this study is the Theory of Legal Effectiveness which is included in the Sociological Juridical Theory. The results of this study indicate that in providing legal protection to the rights of crew members, PT Samudera Indonesia has fulfilled the provisions of National and International legislation, namely Law No. 15 of 2016 which is both the ratification and the ratification of the 2006 Maritime Labor Convention (MLC), as the Maritime Labor Law in Indonesia.